Fabricação e caracterização de eletrodos flexíveis visando o desenvolvimento de sensores vestíveis e sistemas microfluídicos integrados - Dias, Anderson Almeida (2020)
The fabrication of electrodes based on graphite and polymers has been attracting the attention of the scientific community due to some advantages, such as flexibility, facility to assemble, low cost, the possibility of wearable sensors development, and integration with microfluidic systems. Nonetheless, most fabrication processes are not environmentally friendly manufacturing, because of the use of toxic reagents. This study describes an alternative method for the fabrication of the flexible electrodes by solid-solid deposition and hot compression using plastic substrates and graphite powder, without the aid of hazardous chemicals. The electrodes were produced by applying hot pressure over the graphite powder the thermal lamination sheet. The manufacturing process for these electrodes has advantages such as low cost (about 1 unit = 0.03 Brazilian real), mechanical resistance, and versatility. The electrodes were characterized by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), Raman spectroscopy, and scanning electron microscopy. These devices exhibited good current repeatability in CV for different electrodes verified by ANOVA statistical analysis. As proof of concept, the modified electrodes with bismuth were integrated into a 3D device and used for zinc analysis in sweat real samples. The modified electrodes showed linearity in a wide concentration range between 50 and 2000 ppb of Zinc (R² = 0.996) and low detection limit (4.31 ppb). The obtained results for the real samples revealed statistical agreement with the reference method (atomic absorption spectroscopy). Besides, the electrodes were integrated into a microfluidic device (µDPE-plastic microdevice with electrochemical detection) which was incorporated together through a 3D printed platform. Preliminary analyzes performed using a redox probe as model showed repeatability with a standard deviation between injections in the range of 2 and 11% and repeatability between µDPEs verified by ANOVA statistical analysis. The devices exhibited low cost (1 unit = 0.05 Brazilian real), analytical frequency of approximately 75 injections per hour, and the use of low volumes of 10 µL. The 3D platform was also accomplished at a low cost (1 unit = 2.50 Brazilian real) and proved to be essential for good repeatability between injections.